Single Machine Scheduling to Minimize Weighted Sum of Completion Times Added with the Maximum Tardiness - A Branch and Bound Approach - Ramadan, Ayda M. (Sulaimani Journal for Pure and Applied Sciences, 2005)
This paper considers the problem of scheduling n jobs on a single machine to minimize total weighted completion times and the maximum tardiness .A branch and bound algorithm is proposed to find ootimal schedule. Our lower bound based on the late and early jobs. Computational experience on problems with to 60 jobs for a special case and 50 jobs for a general case, where {he previous works solve the problem up to 50 and 40 jobs for special and general case respectively .This indicates that the proposed al gorithm is superior to other known algorithms .
Keywords: Keywords Single machine; weighted sum; Branch and bound